2017
DOI: 10.1038/s41598-017-09826-6
|View full text |Cite
|
Sign up to set email alerts
|

An efficient eco advanced oxidation process for phenol mineralization using a 2D/3D nanocomposite photocatalyst and visible light irradiations

Abstract: Nanocomposites (CNTi) with different mass ratios of carbon nitride (C3N4) and TiO2 nanoparticles were prepared hydrothermally. Different characterization techniques were used including X-ray diffraction (XRD), UV-Vis diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS), transmission electron spectroscopy (TEM) and Brunauer-Emmett-Teller (BET). UV-Vis DRS demonstrated that the CNTi nanocomposites exhibited absorption in the visible light range. A sun light - simulated photoexcitation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Further experiments focused on changing the applied pressure during the filtration process of 5 mL of different solutions of rhodamine B and phenol red at different concentrations of 5, 10, and 20 ppm, using a membrane filter (Figure 4a,b). It is worth mentioning that the choice of the concentrations (20 and 10 ppm) was based on the concentrations reported in the literature [7,17,[19][20][21]. A high vacuum (i.e., low pressure and high suction power) enhanced the removal of the dyes in all cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further experiments focused on changing the applied pressure during the filtration process of 5 mL of different solutions of rhodamine B and phenol red at different concentrations of 5, 10, and 20 ppm, using a membrane filter (Figure 4a,b). It is worth mentioning that the choice of the concentrations (20 and 10 ppm) was based on the concentrations reported in the literature [7,17,[19][20][21]. A high vacuum (i.e., low pressure and high suction power) enhanced the removal of the dyes in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…Qianqian et al, Bai et al, and Liu et al have used centrifugation for their nanomaterials; however, these techniques require several media transfers [10][11][12]. Filtration can be achieved using different types of cellulose filter papers and microporous membranes [1,9,[13][14][15][16][17][18]. Among the commonly used membranes are nylon membranes [7,17,[19][20][21] which will be used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…These two materials attracted much attention due to their exceptional electronic features (Wei et al 2011 , Liu et al 2017 ). We proved, earlier, that a photocatalyst from TiO 2 and reduced graphene oxide (rGO) (Al-Kandari et al 2015a , 2015b , Abdullah et al 2016 , Al-Kandari, Abdullah et al 2016 , Al-Kandari, Abdullah et al 2016 , Al-Kandari et al 2017a , 2017b ) degrades a variety of organic compounds efficiently under simulated sunlight. In this respect, we found that 0.1% of rGO with TiO 2 yielded 63% of phenol degradation within 30 min in the presence of an eco-oxidant, H 2 O 2 (Al-Kandari et al 2017a , 2017b ).…”
Section: Introductionmentioning
confidence: 83%
“…Nevertheless, having a high electron-hole recombination rate and wide bandgap energy, TiO 2 cannot be excited under visible light irradiation (λ > 400 nm) [17,18]. To gain insight into this specific issue, intensive research work has been directed towards the development of visible light-responsive TiO 2 with high catalytic activity using co-catalysts such as carbon nitride or reduced graphene oxide (RGO) because of their exceptional electrical properties and controllable structures [17,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%